Pulse Electrodeposition of Copper in the Presence of a Corrosion Reaction. Issue 6 (25th June 2021) - Green, T. A.; Su, X.; Roy, S.
Abstract : This study has examined the pulse electrodeposition of copper from a deep eutectic solvent. Pulse plating parameters were selected using the methodologies originally developed for aqueous solutions, including constraints arising from double layer charging and mass transport effects. Although copper could be deposited under nearly all conditions, in many instances only partial plating was observed and current efficiencies were low. This effect was greatest at low duty cycles and/or when the off-time was long. This phenomenon was attributed to a corrosion (comproportionation) reaction occurring in the off-time. A simple model based on the corrosion reaction being under cathodic mass transport control was developed. While this could explain the main effects, it predicted a corrosion rate that was typically higher than observed. A variety of other models were then explored, the most plausible one indicating that the corrosion rate in the off-time is being controlled by a slow chemical dissolution step. This explained the main observations and predicts that, only for long pulse periods when steady-state conditions are approached, is the corrosion rate under cathodic mass transport control. Finally, it was found that benzotriazole could be employed to substantially reduce the corrosion rate and allow higher current efficiencies to be obtained.